Weekly glucagon‐like peptide‐1 receptor agonist albiglutide as monotherapy improves glycemic parameters in Japanese patients with type 2 diabetes mellitus: A randomized, double‐blind, placebo‐controlled study. Issue 3 (3rd November 2017) - Nino, Antonio; Okuda, Inaha; Wilson, Timothy H; Yue, Lynn; Nakajima, Hiromu; Tsuboi, Maho; Carr, Molly C; Seino, Yutaka
Abstract: Aims/Introduction: The present phase 3, randomized, double‐blind 24‐week study with extension to 1 year assessed the efficacy and safety of albiglutide compared with placebo in Japanese patients with type 2 diabetes mellitus inadequately controlled by diet and exercise with or without a single oral antidiabetic drug. Materials and Methods: Patients received weekly albiglutide 30 mg ( n  =   160), albiglutide 50 mg ( n  =   150) or a placebo switched to albiglutide 30 mg after 24 weeks ( n  =   77). Open‐label daily liraglutide 0.9 mg ( n  =   103) was included as a reference. Oral antidiabetic drug use was discontinued before baseline. The primary end‐point was 24‐week change from baseline in glycated hemoglobin (HbA1c). Secondary end‐points included fasting plasma glucose, bodyweight and adverse events. Results: At 24 weeks, mean HbA1c changes from baseline were −1.10, −1.30, and 0.25% for albiglutide 30, 50 mg and placebo, respectively ( P vs placebo <0.0001 for both albiglutide doses), −1.19% for liraglutide. Decreases in HbA1c with albiglutide were sustained through the study. Mean fasting plasma glucose decreased by ≥20 mg/dL, and the mean change in bodyweight was ≤0.5 kg through 1 year across groups. Most commonly reported adverse events were nasopharyngitis, constipation and nausea. The incidence of adverse events was higher in active treatment groups than in the placebo group. Few hypoglycemia events were reported; no patient withdrew as a result of hypoglycemia. No new safety signals were detected. Conclusions: Albiglutide monotherapy achieved clinically significant decreases in HbA1c and fasting plasma glucose with good tolerability in Japanese patients with type 2 diabetes mellitus inadequately controlled by diet and exercise with or without a single oral antidiabetic drug. Abstract : Japanese patients with type 2 diabetes mellitus inadequately controlled by diet and exercise, with or without a single oral antidiabetic drug, were treated with the glucagon‐like protein‐1 receptor agonist albiglutide 30 or 50 mg weekly, as monotherapy, in a randomized, double‐blind, placebo‐controlled trial. Reductions in HbA1c were significantly greater than placebo at the 24‐week primary endpoint, while mean change in body weight was ≤0.5 kg through 1 year across groups. Few hypoglycemia events were reported, and no new safety concerns were detected over 1 year of treatment.